Inhibition of Pim1 kinase, new therapeutic approach in virus-induced asthma exacerbations. Issue 3 (12th February 2016) - Vries, Maaike de; Bedke, Nicole; Smithers, Natalie P.; Loxham, Matthew; Howarth, Peter H.; Nawijn, Martijn C.; Davies, Donna E.
Therapeutic options to treat virus-induced asthma exacerbations are limited and urgently needed. Therefore, we tested Pim1 kinase as potential therapeutic target in human rhinovirus (HRV) infections. We hypothesised that inhibition of Pim1 kinase reduces HRV replication by augmenting the interferon-induced anti-viral response due to increased activity of the janus kinase–signal transducer and activator of transcription (JAK-STAT) pathway. Air–liquid interface (ALI) cultures of primary bronchial epithelial cells (PBECs) from healthy individuals and moderate-to-severe asthmatic volunteers were infected with HRV-16 with or without a specific Pim1 inhibitor; viral replication and induction of anti-viral responses were measured using RT-qPCR. Viral titres were measured by 50% tissue culture infective dose and release of interferon-γ-induced protein 10 (IP-10) and RANTES protein assessed by ELISA. Phosphorylation of STAT-1 was determined using western blotting. Viral replication was reduced in ALI cultures of healthy and asthmatic PBECs treated with the Pim1 inhibitor. Using cultures from healthy donors, enhanced STAT-1 phosphorylation upon inhibition of Pim1 kinase activity resulted in increased mRNA expression of interferon-β, interleukin-29, IP-10 and RANTES 12 h after infection and increased protein levels of IP-10 and RANTES 24 h after infection. We have identified Pim1 kinase as novel target to reduce viral replication in ALI cultures of PBECs. This may open new avenues for therapeutic interventions in virus-induced asthma exacerbations. Pim1 inhibition reduces HRV-16 replication, implying a new therapeutic approach for virus-induced asthma exacerbations http://ow.ly/Xxmy2